me iuuat in gremio doctae legisse puellae: mindful reading in the elegies of Propertius - Franklinos, T (2015)
In a critical climate that privileges the hermeneutic position of a reader of a text over the irretrievable intentions of its author, this thesis challenges the status quo by considering the elegist Propertius as his own first reader. Through an exploration of what I have called 'mindful reading'—how Propertius appears to engage intratextually with his own poetic material, recasting parts of it lexically and thematically—, alongside his interaction with the works of his peers and predecessors and wider cultural discourses, we, as readers, are able to appreciate how he may have understood aspects of his own poetry at a given moment. This particular mode of reading is encouraged, in part, by the repeated treatment of certain themes and ideas by Propertius, and, most conspicuously, by the inherently repetitive nature of the amorous discourse in which he is implicated with Cynthia. There are seven chapters. (1) A rhythm of intratextual reading is established in the generically important funerary elegies of Book I, setting this against the poet's amatory discourse. An analysis of II.i shows that mindful reading is a phenomenon that occurs between, as well as within, books. (2) Consideration is given to editorial division of the canonically named 'Book II', and the ordering of poems; the latter part of the chapter considers the important programmatic elegy, II.xiii. (3) A close reading of III.i and III.ii, and their response to Propertius' predecessors and contemporaries is considered, particularly through a (re)reading of II.xxxiv. (4) Poems treating lovers’ brawls and lucubratio are discussed. (5) Propertius' engagement with Maecenas, and his continued adherence to his poetic creed are explored in III.ix and III.x. (6) The notion that Propertius appears to 'un-write' his amatory discourse with Cynthia through mindful reading in the closing cycle of Book III is treated. (7) The place of Cynthia within Book IV, and the elegist’s generic explorations are explored through mindful reading.